2017
DOI: 10.1016/j.jaac.2017.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Are Social and Communication Difficulties a Risk Factor for the Development of Social Anxiety?

Abstract: ObjectiveSocial anxiety (SA) is a common condition associated with social and communication (SC) difficulties in typically developing young people, as well as those with autism spectrum disorder (ASD). Whether SC difficulties place children at risk for developing SA is unclear. Using a longitudinal design, the present study aimed to disentangle the relationship between SA symptoms and SC difficulties using a population-based sample of 9,491 children from the Avon Longitudinal Study of Parents and Children (ALS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
60
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 37 publications
5
60
0
Order By: Relevance
“…Future work that investigates the potential role of the GABA system are needed particularly given its potential as a targeted treatment (Lozano, Hare, & Hagerman, 2014). This is particularly salient given recent evidence that social communication difficulties in a population-based sample predicted elevated features of social anxiety while social anxiety did not predict later social communication symptoms (Pickard, Rijsdijk, Happé, & Mandy, 2017). …”
Section: Discussionmentioning
confidence: 97%
“…Future work that investigates the potential role of the GABA system are needed particularly given its potential as a targeted treatment (Lozano, Hare, & Hagerman, 2014). This is particularly salient given recent evidence that social communication difficulties in a population-based sample predicted elevated features of social anxiety while social anxiety did not predict later social communication symptoms (Pickard, Rijsdijk, Happé, & Mandy, 2017). …”
Section: Discussionmentioning
confidence: 97%
“…Fourth, we used a heterogeneous clinical comparison group. In future studies, more focused comparisons should be made, to understand whether SPCD is clearly differentiated from the social difficulties seen in other types of psychopathology, such as attention deficit/hyperactivity disorder (St. Pourcain et al., ), conduct problems (Mandy, Skuse, Steer, St Pourcain, & Oliver, ) and social anxiety (Pickard, Rijsdijk, Happé, & Mandy, ).…”
Section: Discussionmentioning
confidence: 99%
“…Considering the association, though debated, between social communication impairment and anxiety in individuals with ASD [910], attention should also be given to underlying mechanisms of social skills training (SST) in treating anxiety and depression in individuals with ASD. SST addresses social processes holistically, integrating didactic lessons, peer modeling, and behavioral rehearsal.…”
Section: Identifying and Engaging Common Factorsmentioning
confidence: 99%
“…Although there has been relatively little longitudinal research, prospective studies have shown that social communication impairment, a hallmark feature of ASD, predicts heightened risk of social anxiety longitudinally among typically developing children [9]. One of the few longitudinal studies with children with ASD found that anxiety predicted social communication impairment; however, social communication deficits did not increase risk for anxiety [10].…”
Section: Introductionmentioning
confidence: 99%